QARAQALPAQ HÁM INGLIS TILLERINDE ERKELETIWSHI-KISHIREYTIWSHI AFFIKS HÁM AFFIKSOIDLARDÍŃ GENDER ÓZGESHELIGI - Sarsenbaeva, Q.M. (SCIENCE and SOCIETY, 2025)
The scientific article presents gender specificities of diminutive affixes and affixoids in Karakalpak and English languages. The specific functions and characteristics of affixes and affixoids used in male and female names are also analyzed.
Keywords: affix; affixoid; diminutives; proper nouns; gender; word formation; morphology